2024
DOI: 10.1021/acs.jmedchem.4c00558
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure–Activity Relationship of Cadazolid: A First-In-Class Quinoxolidinone Antibiotic for the Treatment of Clostridioides difficile Infection

Georg Rueedi,
Philippe Panchaud,
Astrid Friedli
et al.

Abstract: Clostridioides difficile (C. difficile) is one of the leading causes of healthcareassociated infections worldwide. The increasing incidence of strains resistant to currently available therapies highlights the need for alternative treatment options with a novel mode of action. Oxazolidinones that are connected to a quinolone moiety with a pyrrolidine linker, such as compound 1, are reported to exhibit potent broadspectrum antibacterial activity. In an effort to optimize this class of compounds for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A recent study revealed that cadazolid has potent and selective antibacterial activity against clinically important strains of C. difficile and acts by targeting the bacterial protein synthesis machinery. Cadazolid is essentially insoluble in the gastrointestinal tract, a major prerequisite for achieving high drug concentrations at the site of infection as well as minimizing potential side effects due to systemic Cadazolid has now advanced to Phase III clinical trials [144].…”
Section: Current Drug Developments Against C Difficile Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study revealed that cadazolid has potent and selective antibacterial activity against clinically important strains of C. difficile and acts by targeting the bacterial protein synthesis machinery. Cadazolid is essentially insoluble in the gastrointestinal tract, a major prerequisite for achieving high drug concentrations at the site of infection as well as minimizing potential side effects due to systemic Cadazolid has now advanced to Phase III clinical trials [144].…”
Section: Current Drug Developments Against C Difficile Infectionmentioning
confidence: 99%
“…Cadazolid is essentially insoluble in the gastrointestinal tract, a ma jor prerequisite for achieving high drug concentrations at the site of infection as well as minimizing potential side effects due to systemic uptake. Cadazolid has now advanced to Phase III clinical trials [144]. A small library of eleven 4-substituted 2-aminoimidazoles was screened for efficacy against C. difficile, with compounds 17 (MIC50 = 2.5-5 mg/mL), 18 (MIC50 = 5 mg/mL), and 19 (MIC50 = 5 mg/mL) (Figure 8) having the most potent in vitro activities.…”
Section: Current Drug Developments Against C Difficile Infectionmentioning
confidence: 99%
See 1 more Smart Citation